Rac3 induces a molecular pathway triggering breast cancer cell aggressiveness: differences in MDA-MB-231 and MCF-7 breast cancer cell lines - Gest, Caroline (BioMed Central, 2013)
BACKGROUND: Rho GTPases are involved in cellular functions relevant to cancer. The roles of RhoA and Rac1 have already been established. However, the role of Rac3 in cancer aggressiveness is less well understood. METHODS: This work was conducted to analyze the implication of Rac3 in the aggressiveness of two breast cancer cell lines, MDA-MB-231 and MCF-7: both express Rac3, but MDA-MB-231 expresses more activated RhoA. The effect of Rac3 in cancer cells was also compared with its effect on the non-tumorigenic mammary epithelial cells MCF-10A. We analyzed the consequences of Rac3 depletion by anti-Rac3 siRNA. RESULTS: Firstly, we analyzed the effects of Rac3 depletion on the breast cancer cells’ aggressiveness. In the invasive MDA-MB-231 cells, Rac3 inhibition caused a marked reduction of both invasion (40%) and cell adhesion to collagen (84%), accompanied by an increase in TNF-induced apoptosis (72%). This indicates that Rac3 is involved in the cancer cells’ aggressiveness. Secondly, we investigated the effects of Rac3 inhibition on the expression and activation of related signaling molecules, including NF-κB and ERK. Cytokine secretion profiles were also analyzed. In the non-invasive MCF-7 line; Rac3 did not influence any of the parameters of aggressiveness. CONCLUSIONS: This discrepancy between the effects of Rac3 knockdown in the two cell lines could be explained as follows: in the MDA-MB-231 line, the Rac3-dependent aggressiveness of the cancer cells is due to the Rac3/ERK-2/NF-κB signaling pathway, which is responsible for MMP-9, interleukin-6, -8 and GRO secretion, as well as the resistance to TNF-induced apoptosis, whereas in the MCF-7 line, this pathway is not functional because of the low expression of NF-κB subunits in these cells. Rac3 may be a potent target for inhibiting aggressive breast cancer.